Purification of damson plum polyphenol oxidase by affinity chromatography and investigation of metal effects on enzyme activity - Yildiz, Selinnur; Bilen, Cigdem; Karakus, Emine (TAYLOR & FRANCIS INC, 2022)
Polyphenol oxidase (PPO) was firstly purified from damson plum as a high antioxidant source. PPO was treated by 0-80% ammonium sulfate precipitation and dialysis. Characterization results were determined for catechol, 4-methyl catechol, pyrogallol and caffeic acid as 0.05 M/pH: 7.2/25 degrees C; 0.2 M/pH: 4.5/10 degrees C; 0.01 M/pH: 6.8/5 degrees C, and 0.2 M/pH: 8.5/10 degrees C, respectively. V-max and K-M values were calculated for same substrates as 17,219.97 U/(mL*min) and 11.67 mM; 7309.72 U/(mL*min) and 5 mM; 12,580.12 U/(mL*min) and 3.74 mM; 12,100.41 U/(mL*min) and 6.25 mM, respectively. Catechol gave the highest V-max value among substrates. Affinity purification was performed by using Sepharose 4B-L-Tyrosine-p-aminobenzoic acid and Sepharose 6B-L-Tyrosine-p-aminobenzoic acid. Single bands were approximately observed at 50 kDa for each affinity sample in SDS-PAGE and Native-PAGE. 93.88 and 10.46 purification-folds were obtained for PPO by reference Sepharose-4B and original Sepharose-6B gels. Metal effects upon PPO activity were also investigated due to the importance of enzymatic browning in foods. Cu+2 activation and Fe+2 inhibition were observed with a final metal concentration of 1 mM at 219.66 and 43.18%, respectively. PPO purification from damson plum by affinity chromatography, its characterization, stability evaluation by statistically, and effects of metal ions on damson plum PPO have not been investigated in the literature.
Keywords: Characterization; damson plum; inhibition; polyphenol oxidase; purifications; SUBSTRATE-SPECIFICITY; FRUIT; PROTEINS; POTATO; EXTRACTION; INDUCTION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology